Influence of Stator and Rotor Slots Combination on Induction Motor Performance - Nory, Hayatullah; Yildiz, Ahmet; Aksun, Serhat; Aksoy, Cansu (Institute of Electrical and Electronics Engineers Inc., 2024)
Electric motors have a wide range of applications in the industry, and there are various types of these motors that offer different design features and functionalities. Among this diversity, induction motors stand out as a prominent motor type due to their widespread use and durability. Although induction motors are widely used, stator and rotor slots combination selection is still a challenge. In this study, the performance of two different three-phase squirrel cage induction motor models with 15 kW, 4 poles, 36 stator slots and 28 and 44 rotor slots, respectively, is examined. Models are analyzed with a computer-based analysis software. As a result of the analysis, the output performances of induction motor models are examined. Analysis results show that incorrect slot combinations selection reduces motor efficiency and causes synchronous torque. As a result of the study, the effects of correct and incorrect stator-rotor slots combination selection on induction motor performance are discussed. © 2024 IEEE.
3rd IEEE International Conference on Power Electronics, Intelligent Control and Energy Systems, ICPEICES 2024 -- 26 April 2024 through 28 April 2024 -- Delhi -- 203533
Keywords: motor performance; slot number combination; squirrel cage induction motor; synchronous torque